2011
DOI: 10.1152/japplphysiol.00287.2010
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects ofAPOEhaplotype, sex, and exercise on postheparin plasma lipase activities

Abstract: Hepatic lipase (HL) and lipoprotein lipase (LPL) activities (HLA, LPLA) modify lipoproteins and facilitate their binding to hepatic receptors. Apolipoprotein E (APOE) physically interacts with the lipases, and the three common haplotypes of the APOE gene (ε2, ε3, and ε4) yield protein isoforms (E2, E3, and E4, respectively) that are functionally different. Lipase activities themselves differ by sex and exercise training status. The interaction of APOE genotype, exercise training, and sex effects on lipase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In contrast to body weight and fat mass, the limited literature data on APOE genotype and energy metabolism is more consistent. There is evidence that individuals carrying ε3/ε4 have greater increase in maximum oxygen consumption (VO 2max ) in response to training than homozygous ε3 carriers though baseline VO 2max were not significantly different . VO 2max is a marker of exercise performance and thus related to mitochondrial performance and energy metabolism, e.g., in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to body weight and fat mass, the limited literature data on APOE genotype and energy metabolism is more consistent. There is evidence that individuals carrying ε3/ε4 have greater increase in maximum oxygen consumption (VO 2max ) in response to training than homozygous ε3 carriers though baseline VO 2max were not significantly different . VO 2max is a marker of exercise performance and thus related to mitochondrial performance and energy metabolism, e.g., in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found LPL activity to be increased [ 30 - 32 ] but also unchanged [ 33 , 34 ] in the early post-exercise period, increased [ 12 ] and unchanged [ 11 ] on the morning after exercise. Other studies have reported increases in LPL activity that are restricted to certain muscle fibre types [ 19 ], timepoints [ 35 ], genders [ 36 ] and apo E haplotypes [ 37 ]. In this recent genetic study [ 37 ], exercise training actually reduced post-heparin LPL activity in the most common apo E haplotype, though this did not prevent a reduction in serum TG.…”
Section: Discussionmentioning
confidence: 99%
“…During the past year, one study with a large sample size examined the interaction of genetic markers identified through GWAS with physical activity and high-density lipoprotein cholesterol (HDL-C) levels (1), while two studies with small sample sizes analyzed the associations between genetic markers and exercise-related adaptations of lipid and lipoprotein metabolism (10,40).…”
Section: Lipid and Lipoprotein Metabolismmentioning
confidence: 99%
“…In another study, Seip et al (40) measured postheparin plasma lipase activities in sedentary normolipidemic men and women with the three most common apolipoprotein (APOE) haplotypes, ε2/ε3 (n = 53), ε3/ε3 (n = 62), and ε4/ε3 (n = 52), enrolled in 6 months of standardized aerobic exercise training. Exercise training decreased LPL activity in the APOE 3/3 haplotype compared with increases in haplotypes 2/3 and 4/3, independent of sex, with this difference being significant only after correcting for baseline insulin (40). However, although both studies are based on standardized exercise intervention protocols, they suffer from the limitation of small sample sizes.…”
Section: Lipid and Lipoprotein Metabolismmentioning
confidence: 99%